Molecular characterization revealed the role of thaumatin-like proteins of Rhizoctonia solani AG4-JY in inducing maize disease resistance - Liu, Jiayue; Feng, Shang; Liu, Tingting; Mao, Yanan; Shen, Shen; Liu, Yuwei; Hao, Zhimin; Li, Zhiyong (Frontiers in Microbiology, 2024)
The gene family of Thaumatin-like proteins (TLPs) plays a crucial role in the adaptation of organisms to environmental stresses. In recent years, fungal secreted proteins (SP) with inducing disease resistance activity in plants have emerged as important elicitors in the control of fungal diseases. Identifying SPs with inducing disease resistance activity and studying their mechanisms are crucial for controlling sheath blight. In the present study, 10 proteins containing the thaumatin-like domain were identified in strain AG4-JY of Rhizoctonia solani and eight of the 10 proteins had signal peptides. Analysis of the TLP genes of the 10 different anastomosis groups (AGs) showed that the evolutionary relationship of the TLP gene was consistent with that between different AGs of R. solani. Furthermore, it was found that RsTLP3, RsTLP9 and RsTLP10 were regarded as secreted proteins for their signaling peptides exhibited secretory activity. Prokaryotic expression and enzyme activity analysis revealed that the three secreted proteins possess glycoside hydrolase activity, suggesting they belong to the TLP family. Additionally, spraying the crude enzyme solution of the three TLP proteins could enhance maize resistance to sheath blight. Further analysis showed that genes associated with the salicylic acid and ethylene pathways were up-regulated following RsTLP3 application. The results indicated that RsTLP3 had a good application prospect in biological control.